THE TEACHER’ ROLE IN EDIFYING THE STUDENT CHARACTER SD INPRES 3 TONDO - Safitri Juniawati; Arif Firmansyah (Universitas Tadulako, 2022)
The purpose of this study was to determine the role of teachers in fostering the character of students in SD Inpres 3 Tondo, to find out the inhibiting factors in fostering the character of student in SD Inpres 3 Tondo. This study uses a qualitative descriptive research model. Research subjects were 20 student data collection techniques used were interviews, quastionnaires, observation and documentation. The results of the study show that : the role of the teacher in fostering the character of students in SD Inpres 3 Tondo has not been implemented optimally, because there are still many students themselves, the efforts made by teachers in SD Inpres 3 Tondo in coaching character that is, using the exemplary approach and familiarizing the character of discipline, religious, independent and responsible. Inhibiting factors of the teacher’s role in fostering character, namely the influence of peer interaction both at school and in the communication with parents of student.